2018
DOI: 10.1111/ffe.12956
|View full text |Cite
|
Sign up to set email alerts
|

A notch critical plane approach of multiaxial fatigue life prediction for metallic notched specimens

Abstract: An approach based on the local stress response is proposed to locate the fatigue critical point for metallic blunt notched specimens under multiaxial fatigue loading. According to the stress analysis, both stress gradient and gradient of loading nonproportionality exist at notch root. The plane in the vicinity of the notch that passes through the fatigue critical point and experiences the maximum shear stress amplitude is defined as the critical plane for notch specimens (CPN). Furthermore, the Susmel's fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Recently, Luo et al combined the CPA and the TCD for fatigue life prediction of thin‐walled notched specimens with a circular hole. According to the physical mechanism that fatigue crack initiation is dominated by shear stress (slips bands formation), the critical plane is settled as the plane that passes through the fatigue critical point and is defined by the maximal shear stress amplitude.…”
Section: Critical Distance Theory and Its Applications To Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Luo et al combined the CPA and the TCD for fatigue life prediction of thin‐walled notched specimens with a circular hole. According to the physical mechanism that fatigue crack initiation is dominated by shear stress (slips bands formation), the critical plane is settled as the plane that passes through the fatigue critical point and is defined by the maximal shear stress amplitude.…”
Section: Critical Distance Theory and Its Applications To Fatiguementioning
confidence: 99%
“…Moreover, by combining the TCD and multiaxial fatigue models (like FS 104,105 and Carpinteri criteria 106-108 ), they further developed a model that can incorporate the impact of mean stress into the fatigue strength calculation and noted that LM is overall more accurate than PM, especially in those cases where high stress gradients occur. 109 Recently, Luo et al 110 combined the CPA and the TCD for fatigue life prediction of thin-walled notched specimens with a circular hole. According to the physical mechanism that fatigue crack initiation is dominated by shear stress (slips bands formation), the critical plane is settled as the plane that passes through the fatigue critical point and is defined by the maximal shear stress amplitude.…”
Section: Critical Distance Theory and Its Applications To Fatiguementioning
confidence: 99%
“…There have been numerous researches on prediction approaches for fatigue life of crack initiation [1,2]. From the view of fatigue damage parameters, these approaches can be divided into stress-based approaches, strain-based approaches and energy density-based approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Although the calculation process is simple, the characteristics of non‐proportional fatigue loading are not considered in this way. Many fatigue tests have shown that the fatigue critical point of notched components under multiaxial fatigue loading is obviously different from that under uniaxial fatigue loading.…”
Section: Introductionmentioning
confidence: 99%